2020
DOI: 10.3390/jcm9040959
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral, Immunomodulatory and Antiproliferative Activities of Recombinant Soluble IFNAR2 without IFN-ß Mediation

Abstract: Soluble receptors of cytokines are able to modify cytokine activities and therefore the immune system, and some have intrinsic biological activities without mediation from their cytokines. The soluble interferon beta (IFN-ß) receptor is generated through alternative splicing of IFNAR2 and has both agonist and antagonist properties for IFN-ß, but its role is unknown. We previously demonstrated that a recombinant human soluble IFN-ß receptor showed intrinsic therapeutic efficacy in a mouse model of multiple scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Notably, IFNAR2 is capable of producing soluble receptors, which binds and regulates endogenous production of type I IFNs ( 17 , 18 ). This soluble IFNAR2 possesses both anti-proliferative and antiviral functions as well as therapeutic properties ( 19 ). In particular, in COVID-19, a protective role of IFNAR2 has been suggested ( 6 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, IFNAR2 is capable of producing soluble receptors, which binds and regulates endogenous production of type I IFNs ( 17 , 18 ). This soluble IFNAR2 possesses both anti-proliferative and antiviral functions as well as therapeutic properties ( 19 ). In particular, in COVID-19, a protective role of IFNAR2 has been suggested ( 6 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, its role in the immune system is mostly unknown, despite that the human form was first cloned in 1995 ( 15 ). Therefore, we cloned a recombinant form analogous to human soluble IFNAR2 and recently demonstrated that it exerts antiviral, immunomodulatory and antiproliferative activities without IFN-β mediation ( 35 ). Regarding the native form, we developed an ELISA to detect sIFNAR2 in serum that was analytically validated ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 Host Genetics Initiative (HGI) is constantly updating its GWAS meta-analysis (latest HGI version 6 available at https://www.covid19hg.org/results/r6/) 21 . GWAS have identified various loci associated with susceptibility to infection or severity of COVID-19 22 , which were later confirmed by colocalization analysis 23 or Mendelian Randomization (MR) 24 . The most consistent region identified among several GWAS associated with severe COVID-19 is at 3p21.31 chromosomal region, which includes several genes, including SLC6A20 25 .…”
Section: Introductionmentioning
confidence: 95%